Groundwater Potential Mapping (GWPM) using Analytical Hierarchy Process (AHP) in Bengkulu City, Indonesia (Rudarsko-geološko-naftni zbornik, 2025)
Rapid urbanization and industrial expansion have led to heightened water demand. Groundwater plays a crucial role in urban settings for sanitation, drinking water, and agriculture. This research seeks to assess groundwater potential in Bengkulu City, Indonesia, employing the Analytical Hierarchy Process (AHP). The study incorporates eight primary factors: lineament density, drainage density, precipitation, geomorphology, geology, slope, land cover, and elevation. A multicollinearity test confirmed the absence of multicollinearity among these parameters. The pairwise comparison matrix produced a consistency ratio of 0.098 (9.8%), indicating acceptable consistency in parameter comparisons. Overlay-weighted linear combination (WLC) analysis categorized the groundwater potential into five levels: very high (2.9% or 3.83 km²), high (50.9% or 67.47 km²), moderate (35.2% or 46.71 km²), low (5.2% or 6.88 km²), and very low (5.8% or 7.64 km²). The AHP model yielded strong performance metrics, including a ROC value of 0.89, accuracy of 0.81, MAE of 0.19, RMSE of 0.43, Kappa of 0.62, precision of 0.86, recall of 0.80, and an F1-score of 0.83. Precipitation, lineament density, and drainage density were the key factors affecting groundwater potential. This study shows that the AHP method is highly effective for mapping groundwater potential, especially in urban areas like Bengkulu City. The results can assist in making informed decisions regarding well drilling for drinking water, agricultural purposes, and artificial recharge projects, contributing to sustainable groundwater management in the region.